Pengaruh Teknologi terhadap Kekerasan Seksual di Era Digital: Pendekatan Perlindungan Hukum Perdata, UU ITE dan Ajaran Islam di Desa Bandar Labuhan - Agus, Azwir; Munthe, Riswan; Naldi, Anri (Universitas Pahlawan Tuanku Tambusai, 2026)
The development of digital technology in rural communities has both positive and negative impacts. One major challenge is the increased risk of digital-based sexual violence, such as the spread of immoral content, online harassment, and child exploitation. The lack of digital literacy and legal understanding among rural communities increases vulnerability to these crimes. Legal protection through civil law, the ITE Law, and the strengthening of Islamic religious values are crucial for preventing and addressing cases of sexual violence in the digital era. Partners in Bandar Labuhan Village face several key challenges: low awareness of the dangers of technology-based sexual violence; and limited public understanding of legal protection, both under civil law and the ITE Law. The Community Service Program (PKM) implementation methods include: Education and Socialization: understanding civil law, the ITE Law, and Islamic teachings through seminars, group discussions, and direct community outreach; ongoing digital literacy and legal education; and strengthening collaboration between the community, religious leaders, and village officials.